Critical review of the molecular design progress in non-fullerene electron acceptors towards commercially viable organic solar cells. (26th April 2018) - Wadsworth, Andrew; Moser, Maximilian; Marks, Adam; Little, Mark S.; Gasparini, Nicola; Brabec, Christoph J.; Baran, Derya; McCulloch, Iain
Abstract : A critical analysis of the molecular design strategies employed in the recent progress of non-fullerene electron acceptors for organic photovoltaics. Abstract : Fullerenes have formed an integral part of high performance organic solar cells over the last 20 years, however their inherent limitations in terms of synthetic flexibility, cost and stability have acted as a motivation to develop replacements; the so-called non-fullerene electron acceptors. A rapid evolution of such materials has taken place over the last few years, yielding a number of promising candidates that can exceed the device performance of fullerenes and provide opportunities to improve upon the stability and processability of organic solar cells. In this review we explore the structure–property relationships of a library of non-fullerene acceptors, highlighting the important chemical modifications that have led to progress in the field and provide an outlook for future innovations in electron acceptors for use in organic photovoltaics.